Research on the application of modulated model predictive control in coal mine power quality management based on STATCOM - ZHANG Baojun; MENG Qinglin; LIU Peng; JI Xiang; LIU Wei; ZHANG Dezheng; LU Weiqiang (Gong-kuang zidonghua, 2023)
A large number of power electronic devices and nonlinear loads are connected to the coal mine power grid, causing a large amount of current harmonics and reactive power in the coal mine power grid. It seriously endangers the power quality of the coal mine power grid. The traditional coal mine power quality control strategies mostly use proportional integral (PI) regulators to control static synchronous compensator (STATCOM) to achieve harmonic suppression and reactive power compensation. But their parameters are difficult to adjust and their dynamic response is slow. In order to solve the above problems, a STATCOM control strategy based on modulated model predictive control (M2PC) is proposed. Firstly, the ip-iq method is used to detect the harmonic current and reactive current in the power grid as the reference current for M2PC. Secondly, based on the reference current and STATCOM mathematical model, the duty cycle and sector cost function of the two effective vectors and zero vectors for each sector is calculated. Thirdly, by minimizing the cost function, the optimal sector and the duty cycle of the two optimal effective vectors and zero vectors corresponding to that sector are obtained. Finally, according to the space vector modulation (SVM) method, switching pulses are allocated to achieve a fixed switching frequency. It thereby controls STATCOM to emit compensation current to offset harmonic and reactive currents in the power grid. The simulation and experimental results show that before the adopting of M2PC based STATCOM, the grid side current distortion is severe, the reactive power fluctuation on the grid side is large. The power factor on the grid side fluctuates and is less than 1. After the adopting of M2PC based STATCOM, the total harmonic distortion rate (THD) of the grid side current is significantly reduced due to STATCOM compensating for the harmonic current on the grid side. Moreover, due to STATCOM compensating for the required reactive power of the load, the reactive power on the grid side remains basically 0. The power factor on the grid side remains stable at 1, effectively improving power quality.